Biochar changed the distribution of imidacloprid in a plant–soil–groundwater system. (November 2022) - Yan, Peng; Zou, Zhenhao; Li, Xin; Zhang, Liping; Zhang, Lan; Fu, Jianyu; Wenyan, Han
Abstract: The use of biochar has increased, as its physicochemical properties reduce the adverse effects of pesticides. However, few studies have comprehensively investigated the effects of biochar on the distribution of pesticides in a plant–soil–groundwater system. In this study, a biochar produced from rice straw at 550 °C was chosen, and column experiments with five rated of biochar application (application rates = 0.0, 1.0, 2.0, 3.0, and 4.0% w/w for B0–B4, respectively) were conducted to investigate the capacity of biochar to immobilize imidacloprid (IMI) in soil, thereby decreasing its uptake by plants and leaching from soil into groundwater. Our results showed that IMI in plants, leached from soil, and detected in soil accounted for 3.78, 1.76, and 36.4% of the total IMI input, respectively, and the biochar treatments dramatically decreased the IMI distribution to 0.57, 0.11, and 13.4%, respectively. By contrast, the percentage of undetected IMI increased from 58.1% in the B0 treatment to an average of 86.0% in the biochar treatments. Biochar treatments increased IMI immobilization in soil, which could be related to the increased soil carbon content, surface area, cation exchange capacity. This study indicates that biochar with characters of high surface area and porosity can stabilize IMI and reduce its potential to harm plants and groundwater. Graphical abstract: Image 1 Highlights: The biochar treatments on the distribution of IMI in a plant–soil–groundwater system were analyzed. Biochar reduced IMI accumulation in plants. Biochar decreased the amount of IMI leaching out of soil. Biochar increased the immobilization of IMI.